BELİEFS ON MARİTAL RELATİONSHİP AND PERCEPTIONS OF GENDER IN THE PREDICTION OF MOTHERS' TRADITIONAL MOTHERHOOD ROLE - Pınar Özdemir; Çağla AYOĞLU (International Journal of Eurasia Social Sciences, 2024)
ABSTRACT In the study, the role of perceptions of gender and beliefs on marital relationship in the prediction of mothers' traditional motherhood role was examined. In addition, it was also revealed whether mothers' traditional motherhood role, perceptions of gender and beliefs of marital relationship differed significantly according to their employment status. The participants of the study were 309 married women with children from different provinces of Turkey. In the study, correlation type relational survey model, which is a subtype of quantitative research techniques, was used. The data were collected through Demographic Information Form, Traditional Motherhood Scale, Perception of Gender Scale and Beliefs on Marriage Relationship. Independent samples t-test and multiple regression analysis were used to analyze the data. The findings obtained from the study were analyzed and according to the regression analysis, it was seen that marital relationship beliefs positively and significantly predicted the traditional mothering role. According to this finding, as mothers' negative beliefs about marriage increase, their mothering roles become more traditional. Another finding was that perception of gender negatively and significantly predicted the traditional mothering role. In other words, as the gender perception that mothers attribute to women and men loses its positivity, their mothering roles become more traditional. When the contributions of the variables to the model are analyzed separately, it is seen that beliefs of marital relationship make the largest contribution to the model. In addition, it can be said that the traditional motherhood role of mothers in paid employment is lower than that of mothers not in paid employment. It can be said that working mothers have higher positive gender perceptions than mothers not in paid employment, and their dysfunctional beliefs about marriage are lower than those of mothers not in paid employment. When the findings obtained in the study are evaluated together, it is seen that gender perception and marital relationship beliefs play a role in the prediction of traditional motherhood role, and this situation varies according to whether the mothers are employed or not.